2019
DOI: 10.1371/journal.pone.0214584
|View full text |Cite
|
Sign up to set email alerts
|

Levels of trace elements and potential toxic elements in bovine livers: A trend analysis from 2007 to 2018

Abstract: Trace elements and potential toxic elements were analyzed in bovine livers submitted for autopsy in the Netherlands during the years 2007 to 2018. The age of each animal was recorded. In total, 1544 livers were analyzed for cadmium, cobalt, chromium, copper, iron, molybdenum, nickel, lead, selenium and zinc. Less than 2% of the liver samples were from veal calves. Young animals had significantly higher concentrations of iron and zinc in their livers compared to animals older than one year, while older animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Therefore, the age-related increment of Cr concentration may be attributed to the increased food intake and enhanced metabolism. Overall, variation in plasma trace elements concentration is possibly related to changes in liver elements concentration with age, which is greater in young animals than adults [ 65 ]. In our study, Mg and Ca were reduced at M5.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the age-related increment of Cr concentration may be attributed to the increased food intake and enhanced metabolism. Overall, variation in plasma trace elements concentration is possibly related to changes in liver elements concentration with age, which is greater in young animals than adults [ 65 ]. In our study, Mg and Ca were reduced at M5.…”
Section: Discussionmentioning
confidence: 99%
“…Large herbivores require adequate quantities of both essential macro-minerals and trace minerals from environment for healthy body functions (Suttle 2010;Yoshihara et al 2013;Atmoko 2016;Uniyal et al 2018). While macro-minerals are required by animals in large quantities, excess of trace elements is known to cause poisoning in animals (Counotte et al 2019). The large mammals often visit salt licks to adequate mineral intake (Ajayi and Ogunjobi 2016); meanwhile, proboscis monkeys use habitats around the coastline or near riparian estuary with certain salinity levels.…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of lethal cases reported seems to indicate that intoxication is spreading silently in dairy herds, urging the development of strategies of monitoring herd copper status and amplifying the awareness of farmers about copper toxicity. In fact, monitoring studies carried out on numerous samples from culled cattle collected in slaughterhouses and/or diagnostic laboratories have demonstrated that a large number of cows have hepatic copper concentrations well above the adequate/normal/physiological levels, and that they are at risk of chronic copper toxicity in many countries such as the UK [ 9 , 11 ], New Zealand [ 12 ], the USA [ 13 , 14 , 15 ], the Netherlands [ 16 ] and Spain [ 17 , 18 , 19 , 20 ]. Dairy cattle are most affected, particularly Holstein Friesian [ 11 , 15 ] and Jersey cows [ 12 , 21 ], and available temporal data show an alarming tendency for an increasing incidence of cases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%